STUDI ETNOBOTANI TUMBUHAN OBAT DI LINGKUNGAN MASYARAKAT ADAT KENEGERIAN RUMBIO UNTUK PENGEMBANGAN MODUL PEMBELAJARAN PADA KONSEP KEANEKARAGAMAN HAYATI DI SMA KELAS X - M. Fahmi H M. Fahmi H; Nursal Nursal; Yuslim Fauziah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The study was conducted to collect data about utilization of medicinalplants the indigenous Rumbio Commnunities from July until August 2015. The resultsare used to developing learning module on the concept of Biological Diversity in theSenior High School Grade X. This study consisted of 2 stage, the first stage is the stageof data collection species of medicinal herbs with survey methods (interviews andobservation). Parameters in this study are the types of medicinal plants in theenvironment of indigenous peoples and utilization of Rumbio Communities. Data wereanalyzed with descriptive methods. The second stage is the development of learningmodule of the first stage of the research results. The second stage development moduleADDIE (Analyze, Design, Development, Implementation, and Evaluation) conductedinto 3 stages: analyze, design, development. Results of this study found 73 species of 38families of plants used in traditional medicine in Indigenous Communities Rumbio.Parts of the plant most widely used are the leaves as many as 60 species, habitattraditional medicinal plants are most numerous in the yard as many as 56 species, theefficacy of traditional medicinal plants most, namely to treat gastrointestinal diseases(stomach aches, colds, dysentery, diarrhea and gastritis) as many as 15 species, theprocessing of traditional medicinal plants are most that by boiling as many as 68species, and then how to use traditional medicinal plants are most that by mouth asmuch as 65 species. Results mean learning assessment module validation is valid withthe average assessment is 4.15. Thus, the learning module can be tested on subjects inSenior High School Biology grade X.Keywords: Plant Medicine , Indigenous Rumbio Commnunities, Learning Module.